Pesantren Teachers’ Meaning of Loss Based on Mopo’o Tanggalo Duhelo Values: A Transcendental Phenomenology - Mohamad Anwar Thalib; Nurhayati Ntuka; Rifdayanti Paungan; Rohalia R Tuna (Journal of Islamic Economics (JoIE), 2026)
Introduction: This study originates from the issue that loss theory in Islamic boarding school accounting is predominantly understood in material terms, neglecting cultural and spiritual dimensions embedded in local Gorontalo values. Understanding how teachers in pesantren interpret loss is important because these meanings reflect a unique integration of religiosity and local wisdom. The topic is interesting as it reveals how accounting practices extend beyond financial measures into cultural and transcendental domains. Research Methods: This research employs an interpretive paradigm using a transcendental phenomenological approach. Data were collected through in-depth interviews and observations, and analyzed through five stages: noema, epoche, noesis, intentional analysis, and eidetic reduction. Results: The findings reveal four meanings of loss: (1) material shortage, (2) lack of gratitude, (3) students’ lack of seriousness in learning, and (4) failure to practice knowledge. These meanings reflect the local cultural value of Mopo’o tanggalo duhelo (endurance and patience). Conclusion: Losses in pesantren are not merely financial but also spiritual and cultural. Practically, this study provides a reference for pesantren to manage loss values based on religiosity and local culture. Theoretically, it extends loss accounting by incorporating cultural and transcendental dimensions.